2013
DOI: 10.1159/000352021
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Attenuates Disease Symptoms and Increases Endogenous Myelin Repair by Recruiting Neural Stem Cells and Oligodendrocyte Progenitors in Experimental Autoimmune Encephalomyelitis

Abstract: Background: Inefficient remyelination of demyelinated plaques in multiple sclerosis (MS) leads to secondary axon degeneration and progressive disability. Therapies that potentiate remyelination would be of immense help for managing MS. Objective: Here, we report the effects of valproic acid (VPA) on focal experimental autoimmune encephalomyelitis (fEAE). Methods: fEAE was induced in Wistar rats by immunizing the animals with guinea pig spinal cord homogenate emulsified in complete Freund's adjuvant and with pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…Previous animal studies have suggested that HDAC inhibitors might have a beneficial effect on the progression of EAE . A single study found that despite a beneficial effect on the remyelination and severity of symptoms, VPA appeared to have no effect on the development of EAE symptoms . We found no association between current VPA use and risk of MS, which is compatible with the observation of no protective effect of VPA in the aforementioned animal model of MS.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Previous animal studies have suggested that HDAC inhibitors might have a beneficial effect on the progression of EAE . A single study found that despite a beneficial effect on the remyelination and severity of symptoms, VPA appeared to have no effect on the development of EAE symptoms . We found no association between current VPA use and risk of MS, which is compatible with the observation of no protective effect of VPA in the aforementioned animal model of MS.…”
Section: Discussionsupporting
confidence: 90%
“…Previous animal studies have suggested that HDAC inhibitors might have a beneficial effect on the progression of EAE . A single study found that despite a beneficial effect on the remyelination and severity of symptoms, VPA appeared to have no effect on the development of EAE symptoms .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition, other factors such as bFGF, EGF, and BDNF have also been shown to enhance neurogenesis and eventually enhance functional recovery in animal models of neurological disease (198)(199)(200). Administration of valproic acid has been shown to attenuate symptoms of EAE, and increase endogenous myelin repair by recruiting NSCs and oligodendrocyte progenitors to the lesion sites (201). Moreover, treatment of EAE animals with polymerized nanocurcumin showed promising results in enhancing neuroprotection and myelin repair (202).…”
Section: Endogenous Neural Stem Cell Niche Modulation As a Therapeutimentioning
confidence: 99%